The genus Microbryum (Pottiaceae, Bryophyta) in Argentina - Denise J. Alvarez; Guillermo M. Suárez (Acta Botânica Brasílica, 2023)
Abstract The genus Microbryum is recorded for the first time in Argentina, with a single species Microbryum davallianum. The species differs from others in the genus mainly by stegocarpous capsules, long setae and spore ornamentation. A description, photographs and illustration of the species are provided.